Pemanfaatan Platform Google Dalam Pembelajaran Bahasa Arab di SMA Muhammadiyah 7 Makassar - Aulia AR, Wahyuni; Arsyad, Azhar; Haniah; Sampar (Shaut al Arabiyyah, 2023)
This study aimed to examine the use of the Google platform in learning Arabic, to analyze the factors supporting and limiting this use and to examine the advantages of using the Google platform for class XI students at SMA Muhammadiyah 7 Makassar to learn Arabic. This study was descriptive qualitative in nature. This study's findings revealed familiarity with the Google platform, which includes Google Classroom, Google Meet, Google Forms, Google Slides, and Google Documents. There were two elements involved in the utilization of the Google platform: supporting factors and hindering factors. Network/wifi, smartphones/computers, workshops/training, and google platform applications were the supporting elements for educators, while the supporting factors for students were educators, parents of students, smartphones/computers, internet quota, and google platform applications. The impediments encountered by educators: The limited ability of educators to access the Internet and school facilities, as well as Internet quotas, network instability, and students' lack of awareness as impediments for educators. The advantages of using the Google platform for educators include facilitating the delivery of content, developing an innovative learning method, and saving time. Students were permitted to accept and complete tasks at any time, unrestricted by space or time constraints.